The Diagnosis and Treatment o Dyscalculia. - Haberstroh, Stefan; Schulte-Körne, Gerd (Deutsches Ärzteblatt International, 2019)
Background: 3-7% of all children, adolescents, and adults suffer from dyscalculia. Severe, persistent difficulty performing arithmetical calculations leads to marked impairment in school, at work, and in everyday life and elevates the risk of comorbid mental disorders. The state of the evidence underlying various methods of diagnosing and treating this condition is unclear. Methods: Systematic literature searches were carried out from April 2015 to June 2016 in the Psyclnfo, PSYNDEX, MEDLINE, ProQuest, ERIC, Cochrane Library, ICTRP and MathEduc databases. The main search terms on dyscalculia were the German terms "Rechenstörung," "Rechenschwäche," and "Dyskalkulie" and the English terms "dyscalculia," "math disorder, and "math disability." The data from the retrieved studies were evaluated in a meta-analysis, and corresponding recommendations on the diagnosis and treatment of dyscalculia were jointly issued by the 20 societies and associations that participated in the creation of this guideline. Results: The diagnosis of dyscalculia should only be made if the person in question displays below-average mathematical performance when seen in the context of relevant information from the individual history, test findings, clinical examination, and further psychosocial assessment. The treatment should be directed toward the individual mathematical problem areas. The mean effect size found across all intervention trials was 0.52 (95% confidence interval [0.42; 0.62]). Treatment should be i nitiated early on in the primary-school years and carried out by trained specialists in an individual setting; comorbid symptoms and disorders should also receive attention. Persons with dyscalculia are at elevated risk of having dyslexia as well (odds ratio [OR]: 12.25); the same holds for attention deficit/hyperactivity disorder and for other mental disorders, both internalizing (such as anxiety and depression) and externalizing (e.g., disorders characterized by aggression and rule-breaking). Conclusion: Symptom-specific interventions involving the training of specific mathematical content yield the best results. There is still a need for high-quality intervention trials and for suitable tests and learning programs for older adolescents and adults.